Electrocardiographic findings in patients with arrhythmogenic cardiomyopathy and right bundle branch block ventricular tachycardia. Issue 3 (13th January 2023) - Laredo, Mikael; Tovia-Brodie, Oholi; Milman, Anat; Michowitz, Yoav; Roudijk, Rob W; Peretto, Giovanni; Badenco, Nicolas; te Riele, Anneline S J M; Sala, Simone; Duthoit, Guillaume; Arbelo, Elena; Ninni, Sandro; et al.
Abstract: Aims: Little is known about patients with right bundle branch block (RBBB)-ventricular tachycardia (VT) and arrhythmogenic cardiomyopathy (ACM). Our aims were: (i) to describe electrocardiogram (ECG) characteristics of sinus rhythm (SR) and VT; (ii) to correlate SR with RBBB-VT ECGs; and (iii) to compare VT ECGs with electro-anatomic mapping (EAM) data. Methods and results: From the European Survey on ACM, 70 patients with spontaneous RBBB-VT were included. Putative left ventricular (LV) sites of origin (SOOs) were estimated with a VT-axis-derived methodology and confirmed by EAM data when available. Overall, 49 (70%) patients met definite Task Force Criteria. Low QRS voltage predominated in lateral leads ( n = 37, 55%), but QRS fragmentation was more frequent in inferior leads ( n = 15, 23%). T-wave inversion (TWI) was equally frequent in inferior ( n = 28, 42%) and lateral ( n = 27, 40%) leads. TWI in inferior leads was associated with reduced LV ejection fraction (LVEF; 46 ± 10 vs. 53 ± 8, P = 0.02). Regarding SOOs, the inferior wall harboured 31 (46%) SOOs, followed by the lateral wall ( n = 17, 25%), the anterior wall ( n = 15, 22%), and the septum ( n = 4, 6%). EAM data were available for 16 patients and showed good concordance with the putative SOOs. In all patients with superior-axis RBBB-VT who underwent endo-epicardial VT activation mapping, VT originated from the LV. Conclusions: In patients with ACM and RBBB-VT, RBBB-VTs originated mainly from the inferior and lateral LV walls. SR depolarization and repolarization abnormalities were frequent and associated with underlying variants.